Epigenetic alterations on C1‐inhibitor expression may influence hereditary angioedema attack frequency and C4 levels: Comment on: Karagianni P, Goules AV, Tzioufas AG. Epigenetic alterations in Sjogren's syndrome patient saliva. (5th October 2020) - Khan, S.; Longhurst, H.
Abstract : Epigenetic studies reveal how our genes (nature) are influenced by environment (nurture) leading to wide variability in clinical presentations, especially in autoimmune diseases. Patients with C1‐inhibitor deficiency, even within the same family, have diverse clinical presentations that may reflect epigenetic control of gene expression by hormones or inflammatory signals.